Differences among plantar pressure of acrobatic gymnasts when they jump over two competition floors. Does the presence of mattresses affect the gymnasts` performance? - Paulino, M. F.; Roseiro, L. M.; Dias, J. P.; Neto, M. A.; Amaro, A. M. (Science & Sports, 2021)
The main goal of this study was to investigate the effect of two acrobatic competition floors upon plantar pressures at the gymnasts` feet during landings from two different falling heights. Six competition gymnasts were evaluated, three "bases" and three "tops", with a mean age of 16 years for the bases and 12 years for the tops. Two different commercial landing surfaces (practicable) and two cushion mattresses were used, the jumps were made from two different heights: 0.45 m and 1.15 m. The data acquisition system is based on flexible reference insoles, namely the Pedar Mobile® system (Novel, Germany). The results showed that the type of landing surface as well as the height of the jump have a considerable influence on the values of plantar pressure. Moreover, the presence of the mattresses allowed to reduce significantly the plantar pressure, so the mattresses can be used during the training to avoid the occurrence of injuries. Nevertheless, is clear that the use of additional mattresses over competition floors can increase the mean asymmetry value in about 3.5%, which can be related with changes on athlete performance.